VD_FINDINFO Réc-civile / 2021 / 41 vom 7. Dezember 2021 - VD Tribunal cantonal (2021)
RÉCUSATION, REJET DE LA DEMANDE, DROIT À UNE AUTORITÉ INDÉPENDANTE ET IMPARTIALE | 405 al. 1 CPC (CH), 47 al. 1 let. b CPC (CH), 47 al. 1 let. f CPC (CH), 8a al. 5 CDPJ